Angina pectoris severity and late-life frailty among men with cardiovascular disease. (9th April 2021) - Lutski, Miri; Weinstein, Galit; Tanne, David; Goldbourt, Uri
Abstract: Objective: We investigated the association between severity of angina pectoris (AP) and subsequent late-life frailty among men with cardiovascular disease (CVD). Method: A subset of 351 men (mean age at baseline 56.7 ± 6.5 years) who previously participated in the Bezafibrate Infarction Prevention, BIP trial (1990–1997) underwent a neurovascular evaluation as part of the BIP Neurocognitive study 15.0 ± 3.0 years after baseline (T1) and a frailty evaluation according to Fried 19.9 ± 1.0 years after baseline (T2). Severity of AP was assessed at baseline of the BIP trial using the Canadian Cardiovascular Society angina classification. We assessed the odds of being in the advanced rank of frailty status (robust, pre-frail, and frail) using ordered logistic regression. Results: Among 351 participants, 134 (38.2%) were classified as pre-frail and 100 (28.5%) as frail. Frailty was found among 42% participants in the AP class ≥2 and among 26% participants in the AP class <2. Adjusting for demographic, health-related and cognitive variables, odds ratio (OR), and 95% confidence interval (95% CI) for advanced rank of frailty was 2.68 (95% CI: 1.29–5.59) comparing AP class ≥2 to AP class <2. Discussion: Among men with CVD, severity of AP should be taken into risk consideration due to its strong association with late-life frailty, particularly among inactive participants and participants with cerebral microvascular damage.